Elevated expression of the RNA-binding protein IGF2BP1 enhances the mRNA stability of INHBA to promote the invasion and migration of esophageal squamous cancer cells - Juan-Juan Wang; Ding-Xiong Chen; Yu Zhang; Xin Xu; Yan Cai; Wen-Qiang Wei; Jia-Jie Hao; Ming-Rong Wang (Experimental Hematology & Oncology, 2023)
Abstract Background The mechanisms underlying the occurrence and development of esophageal squamous cell carcinoma (ESCC) remains to be elucidated. The present study aims to investigate the roles and implications of IGF2BP1 overexpression in ESCC. Methods IGF2BP1 protein expression in ESCC samples was assessed by immunohistochemistry (IHC), and the mRNA abundance of IGF2BP1 and INHBA was analyzed with TCGA datasets and by RNA in situ hybridization (RISH). The methylation level of the IGF2BP1 promoter region was detected by methylation-specific PCR (MSP-PCR). Cell viability, migration, invasion and in vivo metastasis assays were performed to explore the roles of IGF2BP1 overexpression in ESCC. RNA immunoprecipitation sequencing (RIP-seq) and mass spectrometry were applied to identify the target RNAs and interacting proteins of IGF2BP1, respectively. RIP-PCR, RNA pulldown, immunofluorescence (IF), gene-specific m6A PCR and RNA stability assays were used to uncover the molecular mechanisms underlying the malignant phenotypes of ESCC cells caused by IGF2BP1 dysregulation. BTYNB, a small molecular inhibitor of IGF2BP1, was evaluated for its inhibitory effect on the malignant phenotypes of ESCC cells. Results IGF2BP1 overexpression was detected in ESCC tissues and associated with the depth of tumor invasion. In addition, IGF2BP1 mRNA expression in ESCC cells was negatively correlated with the level of its promoter methylation. Knockdown of IGF2BP1 inhibited ESCC cell invasion and migration as well as tumor metastasis. Mechanistically, we observed that IGF2BP1 bound and stabilized INHBA mRNA and then resulted in higher protein expression of INHBA, leading to the activation of Smad2/3 signaling, thus promoting malignant phenotypes. The mRNA level of INHBA was upregulated in ESCC tissues as well. Furthermore, IGF2BP1 interacted with G3BP stress granule assembly factor 1 (G3BP1). Knockdown of G3BP1 also down-regulated the INHBA-Smad2/3 signaling. BTYNB abolished this activated signaling and significantly attenuated the malignant phenotypes of ESCC cells. Conclusions Elevated expression of IGF2BP1 is a frequent event in ESCC tissues and might be a candidate biomarker for the disease. IGF2BP1 overexpression promotes the invasion and migration of ESCC cells by activating the INHBA-Smad2/3 pathway, providing a potential therapeutic target for ESCC patients with high expression of IGF2BP1.